Improving nitrogen use efficiency by manipulating nitrate remobilization in plants - Chen, Kuo-En; Chen, Hui-Yu; Tseng, Ching-Shan; Tsay, Yi-Fang (Nature plants, 2020)
Increasing nitrogen use efficiency (NUE) is critical to improve crop yield, reduce N fertilizer demand and alleviate environmental pollution. N remobilization is a key component of NUE. The nitrate transporter NRT1.7 is responsible for loading excess nitrate stored in source leaves into phloem and facilitates nitrate allocation to sink leaves. Under N starvation, the nrt1.7 mutant exhibits growth retardation, indicating that NRT1.7-mediated source-to-sink remobilization of stored nitrate is important for sustaining growth in plants. To energize NRT1.7-mediated nitrate recycling, we introduced a hyperactive chimeric nitrate transporter NC4N driven by the NRT1.7 promoter into the nrt1.7 mutant. NRT1.7p::NC4N::3 ′ transgenic plants accumulated more nitrate in younger leaves, and 15 NO 3 − tracing analysis revealed that more 15 N was remobilized into sink tissues. Consistently, transgenic Arabidopsis , tobacco and rice plants showed improved growth or yield. Our study suggests that enhancing source-to-sink nitrate remobilization represents a new strategy for enhancing NUE and crop production. One important direction to reduce the application of nitrogen fertilizer is to improve nitrogen use efficiency (NUE) of crops. Now an interesting strategy that engineers the transporter responsible for source-to-sink nitrate remobilization is employed to generate transgenic Arabidopsis , tobacco and rice lines with enhanced NUE and plant yield.